(untitled) (Damascus University Journal of arts and humanities sciences, 2023)
The image of the other (Arabic) in the French travel literature Madame Diolavua’s journey from Muhammarah to Basra and Baghdad in the year 1881AD-1299AH (model) Abstract In this research, I tried to capture the features of the Arab identity as a national identity present in the French travel literature; In the beginning, it was necessary to quickly refer to the linguistic meanings of the other and its idiomatic dimensions, then the research sought to trace the themes of the manifestation of the image of the Arabs in Madame Diolavo’s journey from Muhammarah to Basra and Baghdad in the year 1881 AD-1299 AH, the writer was able to portray various social, economic and social aspects, or even Those that are related to the nature of the relationship between the components of the Arab-Islamic society in the areas it visited, and the research did not neglect - during the narration of the pictorial topics - monitoring the literary sources in the pictures it transmitted, as well as highlighting the patterns, forms and reasons for photography, and the research also shed light on some distorted images. And the reasons for this distortion.